Rancang Bangun Alat Resusitasi Jantung Paru Portable Berbasis Arduino Uno Atmega 328 - Wahyudin; Syam, Rafiuddin; Maruddani, Baso (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2024)
The purpose of this research is to design a portable cardiopulmonary resuscitation device based on Arduino Uno Atmega 328 to help provide first aid to people experiencing sudden cardiac arrest and minimize the occurrence of deaths due to sudden cardiac arrest due to slow assistance to victims experiencing sudden cardiac arrest. The design is carried out by creating a device based on the Arduino Uno Atmega 328 microcontroller and using a DC motor as a driver. This device is equipped with a pulse heart sensor to detect the pulse which will be displayed on a 16x2 LCD. The research was conducted using the Research & Development method by testing the accuracy of pulse readings, torque, and compression pressure. The advantages of the system are that it is easy to use and easy to carry anywhere. The results of the study show that the system created is capable of performing compressions at a speed of 80 times per minute. This device can also read the pulse with an error percentage of 1.29% when compared to an oximeter.